Entwurf hochdynamischer Sensor- und Regelsysteme für die adaptive Laserbearbeitung - Hohenstein, Ralph (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2004)
The vision, that a laser system adapts and controls all process variables; such as beam power, focus, feed rate, etc., in real-time, is in need of a name: adaptive laser processing. This work devises the essential steps for the development of systems, which provide the laser with the sensory, logical and learning abilities relevant to adaptive laser processin